Characteristics Associated With Mexican-American Hospice Use: Retrospective Cohort Study Using the Hispanic Established Population for the Epidemiologic Study of the Elderly (H-EPESE). (May 2023) - Shepard, Victoria; Al Snih, Soham; Burke, Rebecca; Downer, Brian; Kuo, Yong-Fang; Malagaris, Ioannis; Raji, Mukaila
Background: Hospice use is lower among ethnic/racial minorities in the United States, though little is known about trends, associated factors and duration of hospice use by Mexican-Americans. Aim: The purpose of this study is to examine Mexican-American characteristics associated with hospice stay, both ≤ and > 7 days. Design: This retrospective cohort study used data from the Hispanic Established Population for the Epidemiological Study of the Elderly (H-EPESE) and the Centers for Medicare and Medicaid Services. Multivariate logistic regression models were used to estimate the ORs and 95% CIs for hospice stay among Mexican-Americans, both ≤ and > 7 days. Setting and participants: The first cohort (N = 970) includes H-EPESE participants who died between 2004 and 2016 who had Medicare parts A and B. The second cohort (N = 403) includes participants who completed the H-EPESE survey within the last 2 years of life. Results: Although hospice use increased among Mexican-Americans between 2004 and 2016 (OR 1.88, 95% CI 1.19-2.97), 38% of participants died within the first week of hospice care. Mexican-Americans in New Mexico and Arizona were 2-4 times more likely to use hospice than those in Texas and Colorado. Dementia was associated with hospice use (OR 1.47, 95% CI 1.11-1.94). Characteristics, like church attendance and living alone, were not associated with hospice use. Conclusions: The substantial proportion of Mexican-Americans with 7 days or less of hospice use underscores the need for early palliative/hospice intervention to mitigate variation in use.